Environmental cost benefit analysis of the use of green technologies in irrigated agriculture : a case study of Mashare Irrigation Farm in Kavango East Region, Namibia - Ankama, Ankama Nadagho (Stellenbosch : Stellenbosch University, 2025)
Thesis (MPhil)--Stellenbosch University, 2024.